The Impact of the COVID-19 Pandemic on the Residency Experience: A Qualitative Study - Hyman, Joshua; Doolittle, Benjamin (International Journal of Innovative Research in Medical Science, 2023)
Objective: The COVID-19 pandemic has greatly impacted the residency experience, yet few qualitative studies have engaged residents for their perspectives. Our aim in this investigation was to better understand what effect the COVID-19 pandemic has had on resident learning climate and well-being and to determine how perspectives on the residency experience have changed over time. Methods: We conducted interviews from May 2020 through February 2021 with residents from the internal medicine, pediatrics, and internal medicine-pediatrics residency programs from a single, university-affiliated hospital. Validated instruments were used to quantify participants’ level of satisfaction and burnout. A snowball sampling technique was used for recruitment. We employed thematic content analysis using a grounded theory-based approach. Results: Of the 56 residents invited to participate, 37 (66.1%) elected to do so. The first 15 interviews were completed between May 2020 and July 2020 (early COVID-19), with 22 interviews completed between December 2020 and February 2021 (late COVID-19). The residents interviewed during the late COVID-19 block were less likely to meet criteria for satisfaction (p<0.01) and thriving (p<0.05) and were more likely to endorse feeling burned out (p<0.002) compared to their peers in the early COVID-19 cohort. Four key themes emerged: changes to training and education, changes to well-being, changes to the practice of medicine, and changes to perspectives on residency. Conclusions: Residents described how the COVID-19 pandemic has contributed to a diminished sense of well-being as well as poorer clinical training. Further study should be done to determine what measures can be taken to help attenuate COVID-19-related burnout and educational compromise.